Unilateral coercive measures in the doctrine of modern international law - A. V. Chuck (Вестник университета)
The main purpose of this article was to study the theoretical foundations of the application of unilateral coercive measures by states. It was determined that these measures are not consistent with all the fundamental international legal principles. The author indicates that such measures have a wide range of actions and can be both economic and non-economic by nature. The terminological problem of the concept of “unilateral coercive measures” is considered. These measures are often mistakenly referred to as “sanctions”, thereby identifying them with unquestionably legitimate measures taken by the United Nations Security Council. In the legislation of the Russian Federation, unlike other states, there was no confusion of concepts. The article notes that the issue of the legality of the use of unilateral coercive measures is relevant. The fact is that these measures, among other things, can negatively affect the lives of innocent citizens. The most vulnerable segments of society are particularly affected by this, for example, due to the denial of access to essential goods. For this reason, unilateral coercive measures taken by a state should not create any serious violations of people’s fundamental rights. In addition, due to their specific nature, unilateral coercive measures affect the economic processes of states.